Strengthening Teacher Competencies in the Era of Independent Curriculum through the Implementation of Change Management - Laili Komariyah; Nurul Fitriyah Sulaeman; Atin Nuryadin (Universitas Lambung Mangkurat, 2024)
: This community service aimed to strengthen teachers' competencies in dealing with curriculum changes from the 2013 curriculum to the independent curriculum through training in the application of change management. This service activity is carried out using an asset-based community development (ABCD) approach, strengthening participants' potential for responding to change. The training participants were 35 elementary school teachers in Samarinda City. Training activities were conducted at SD Negeri 007 Samarinda Ulu, Samarinda City. This activity was carried out on Saturday, July 29, 2023. The activities involved providing training to strengthen teacher competencies by explaining the application of change management in dealing with curriculum changes. Data on training outcomes were obtained through the Teacher Attitudes Towards Change Scale (TATCS) questionnaire and questions regarding participants' perceptions of the training. Participants' answers were analyzed using keywords and word co-occurrence analyses. The training strengthened teacher competence in the era of an independent curriculum by increasing teacher belief in the importance of curriculum change, confidence in applying the Merdeka curriculum, and support for curriculum change. These results indicate the urgency of conducting similar training periodically to strengthen teacher competence in the adaptation process using an independent curriculum.